2011
DOI: 10.1007/s10468-011-9276-4
|View full text |Cite
|
Sign up to set email alerts
|

Rings of Idempotent Stable Range One

Abstract: We show that in a ring of stable range 1, any (von Neumann) regular element is clean. Our main results also imply that any unit-regular ring has idempotent stable range 1 (and is therefore clean), and that a semilocal ring has idempotent stable range 1 if and only if it is semiperfect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Unit-endoregular modules are studied recently in [28] which provided some examples and characterizations. In this paper, we provide more characterizations of unit-endoregular modules generalizing results for unit-regular rings (see e.g., Camillo and Khurana [2], Henriksen [12], Wang et al [24]). Although a direct sum of unit-endoregular modules need not be a unit-endoregular module in general, by using the notion of relative endoregularity we provide sufficient and necessary conditions under which the direct sums of unit-endoregular modules are unit-endoregular.…”
Section: Introductionmentioning
confidence: 80%
“…Unit-endoregular modules are studied recently in [28] which provided some examples and characterizations. In this paper, we provide more characterizations of unit-endoregular modules generalizing results for unit-regular rings (see e.g., Camillo and Khurana [2], Henriksen [12], Wang et al [24]). Although a direct sum of unit-endoregular modules need not be a unit-endoregular module in general, by using the notion of relative endoregularity we provide sufficient and necessary conditions under which the direct sums of unit-endoregular modules are unit-endoregular.…”
Section: Introductionmentioning
confidence: 80%
“…(2) Lemma 3.3 provides an easy way to see that regular elements in rings with stable range one are always clean, which was originally proved in [21,Theorem 3.3].…”
Section: Element-wise Connections Between Unit-regularity and Clean Dmentioning
confidence: 99%
“…Recall that a ring R is said to have idempotent stable range one (written isr(R)=1) provided that for any a, b ∈ R, aR + bR = R implies that a + be ∈ U (R) for some e ∈ Id(R) (see [6,16]). If e is an arbitrary element of R (not necessary an idempotent), then R is said to have stable range one.…”
Section: Stable Range Conditionsmentioning
confidence: 99%
“…Clean rings were introduced by Nicholson in relation to exchange rings and have been extensively studied since then. Recently, Wang et al [16] showed that unit regular rings have idempotent stable range one (i.e., whenever aR + bR = R with a, b ∈ R, there exists e 2 = e ∈ R such that a + be ∈ U (R), written isr(R) = 1 for short), and rings with isr(R) = 1 are clean. In 1999, Nicholson [13] called an element of a ring R strongly clean if it is the sum of a unit and an idempotent that commute with each other, and R is strongly clean if each of its elements is strongly clean.…”
Section: Introductionmentioning
confidence: 99%